Human Leukocyte Antigen Class I and II Knockout Human Induced Pluripotent Stem Cell–Derived Cells: Universal Donor for Cell Therapy. Issue 23 (4th December 2018) - Mattapally, Saidulu; Pawlik, Kevin M.; Fast, Vladimir G.; Zumaquero, Esther; Lund, Frances E.; Randall, Troy D.; Townes, Tim M.; Zhang, Jianyi
Abstract : Background: We aim to generate a line of "universal donor" human induced pluripotent stem cells (hiPSCs) that are nonimmunogenic and, therefore, can be used to derive cell products suitable for allogeneic transplantation. Methods and Results: hiPSCs carrying knockout mutations for 2 key components (β2 microglobulin and class II major histocompatibility class transactivator) of major histocompatibility complexes I and II (ie, human leukocyte antigen [HLA] I/II knockout hiPSCs) were generated using the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR associated protein 9 (Cas9) gene‐editing system and differentiated into cardiomyocytes. Pluripotency‐gene expression and telomerase activity in wild‐type (WT) and HLAI/II knockout hiPSCs, cardiomyocyte marker expression in WT and HLAI/II knockout hiPSC‐derived cardiomyocytes, and assessments of electrophysiological properties (eg, conduction velocity, action‐potential and calcium transient half‐decay times, and calcium transient increase times) in spheroid‐fusions composed of WT and HLAI/II knockout cardiomyocytes, were similar. However, the rates of T‐cell activation before (≈21%) and after (≈24%) exposure to HLAI/II knockout hiPSC‐derived cardiomyocytes were nearly indistinguishable and dramatically lower than after exposure to WT hiPSC‐derived cardiomyocytes (≈75%), and when WT and HLAI/II knockout hiPSC‐derived cardiomyocyte spheroids were cultured with human peripheral blood mononuclear cells, the WT hiPSC‐derived cardiomyocyte spheroids were smaller and displayed contractile irregularities. Finally, expression of HLA‐E and HLA‐F was inhibited in HLAI/II knockout cardiomyocyte spheroids after coculture with human peripheral blood mononuclear cells, although HLA‐G was not inhibited; these results are consistent with the essential role of class II major histocompatibility class transactivator in transcriptional activation of the HLA‐E and HLA‐F genes, but not the HLA‐G gene. Expression of HLA‐G is known to inhibit natural killer cell recognition and killing of cells that lack other HLAs. Conclusions: HLAI/II knockout hiPSCs can be differentiated into cardiomyocytes that induce little or no activity in human immune cells and, consequently, are suitable for allogeneic transplantation.